The Effect of Critical Thinking on Developing EFL Female Learners’ Cognitive Writing Skills at an International Technical College in the KSA - Ahmed, Halima Adlan Khedir Mohmmed (Journal of Cultural Analysis and Social Change, 2026)
The present study aimed to examine the relationship between critical thinking (CT) and cognitive writing performance among tertiary-level EFL female learners, exploring how CT skills can be effectively integrated into the process writing approach and identifying the extent to which CT instruction influences learners’ ability to engage in various stages of the writing process. One pretest and one posttest were administered to the same experimental group of 20 tertiary female students at a technical college. The results showed that CT in EFL pedagogy had a favorable impact on Saudi EFL tertiary students' greatest levels of thinking capacity following the treatment sessions of the CT techniques for writing. Also, the process for the writing approach enhanced the creation of CT abilities for students in an EFL setting. Furthermore, the selected instructional technique for teaching writing skills, which incorporated gradual assessment, was deemed appropriate.